Wales and the Crusades : c. 1095-1291 - Hurlock, Kathryn (Studies in Welsh history., 2011)
This study is the first to consider the impact of the crusades and crusading on medieval Wales. By looking at references to crusading in poetry, chronicles and other literature, examining efforts at recruitment and assessing the levels of participation and interaction, it considers the level of interest in the crusading movement shown in Wales and the Welsh March among the native Welsh and settlers. Support for the military orders and their role in Welsh life, as well the political role of crusading help to highlight the domestic impact a movement focussed in the Latin East had in medieval Wa.